2012
DOI: 10.2118/125095-pa
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Effect of Pressure and Solution Gas on Oil Recovery From Surfactant/Polymer Floods

Abstract: Surfactant/polymer (SP) and alkali/surfactant/polymer flooding is of current interest because of the need to recover residual oil after primary and secondary recovery. If designed properly, these enhanced-oil-recovery processes can give very high oil recoveries. Microemulsion phase behavior plays a central role in process performance and is typically measured by performing salinity scans in glass pipettes at atmospheric pressure and reservoir temperature using dead crude oil from the reservoir of interest. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…These hypotheses are in line with the observation that the lipophilic tendency of surfactant decreases for very light fractions, mostly constitutive of the Gas phase; and they are in agreement with the conjecture of Roshanfekr et al (2012), stating that "other than the change in the Oil composition, free Gas should not affect the phase behavior, but will affect relative permeabilities." They also seem to be supported by recent chemical corefloods with trapped Gas (Farajzadeh et al 2013), considering that mobile Gas is chased by the preflush.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…These hypotheses are in line with the observation that the lipophilic tendency of surfactant decreases for very light fractions, mostly constitutive of the Gas phase; and they are in agreement with the conjecture of Roshanfekr et al (2012), stating that "other than the change in the Oil composition, free Gas should not affect the phase behavior, but will affect relative permeabilities." They also seem to be supported by recent chemical corefloods with trapped Gas (Farajzadeh et al 2013), considering that mobile Gas is chased by the preflush.…”
Section: Introductionsupporting
confidence: 87%
“…Their first goal was to propose a formulation method not requiring corefloods under reservoir pressure; Roshanfekr et al (2012Roshanfekr et al ( , 2013 also started implementing their model in a well-known academic chemical reservoir simulator (UTCHEM, Delshad et al 1996), which previously already included Salager's and Graciaa's correlations ). However, one limitation of UTCHEM is that it does not handle Gas/Oil equilibrium, hence dissolved gas in Oil.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, more papers reported that the optimum salinity of a live oil was lower than that of the respective dead oil. Kahlweit et al (1988), Skauge and Fotland (1990), Sassen et al (1991), Austad and Strand (1996), and Roshanfekr et al (2012) all observed that the increased pressure reduced surfactant solubility in crude oils and the optimum salinity increased. The effect of pressure was opposite to that of added methane (live oil).…”
Section: Figure 1 -Types Of Microemulsions (Surfactant Systems)mentioning
confidence: 91%
“…Cottin et al (2012) reported a slight increase in the optimum salinity of their live oil compared with their dead oil. Puerto and Reed (1983), Roshanfekr et al (2012), and Southwick et al (2012) observed that the optimum salinity decreased when methane was added in oils. Sagi et al (2013) also observed a decrease in the optimum salinity when either methane, ethane or CO2 was added in a dead oil.…”
Section: Figure 1 -Types Of Microemulsions (Surfactant Systems)mentioning
confidence: 97%
“…In this particular study, the variation of the number of POs and EOs in the carboxylate surfactants was the key method used to select the best primary surfactant structure [e.g., the number of POs and EOs in the surfactant was varied to achieve the desired optimal salinity (Bourrel and Schechter 1988;Green and Willhite 1998)]. Cosolvent was used to reduce the microemulsion viscosity and to increase the aqueous solubility of the surfactants at optimal salinity, with the procedures in Sahni et al (2010).…”
Section: Introductionmentioning
confidence: 99%